Effect of N-enriched co-compost on transpiration efficiency and water-use efficiency of maize (Zea mays L.) under controlled irrigation - Adamtey, Noah; Cofie, Olufunke O.; Ofosu-Budu, G.K.; Ofosu-Anim, J.; Laryea, K.B.; Forster, D. (Elsevier, 2010)
Population growth, urban expansion and economic development are increasing competition for water use between agriculture and other users. In addition, the high rate of soil degradation and declining soil moisture in the Sub-Saharan African Region have called for several crop production management and irrigation options to improve soil fertility, reduce water use by crops and produce 'more crops per drop of water'. Notwithstanding this, considerable variations exist in the literature on water-use efficiency, WUEcwu (economic yield per water used) for maize (Zea mays L.) across climates and soil management practices. Different views have been expressed on the effect of different rates of nitrogen (N) application on transpiration efficiency, TE (biomass produced per unit ofwater transpired). The objectives of the study were to assess the effect of different rates of N-enriched municipal waste co-compost and its derivatives on TE, WUEcwu and yield of maize (Z. mays L.) in comparison to inorganic fertiliser. The greenhouse pot experiment was conducted in Accra, Ghana on a sandy loam soil (Ferric Lixisol) using a split plot design. The main plot treatmentswere soil (S), dewatered faecal sludge(DFS), municipal solidwaste compost (C),co-compost from municipal solid waste and dewatered faecal sludge (Co), compost enriched with (NH4)2SO4 (EC), co-compost enriched with (NH4)2SO4 (ECO), (NH4)2SO4 and NPK15-15-15 + (NH4)2SO4. The sub-plot treatments were different rates of application of nitrogen fertiliser applied at the rate of 91, 150 and 210 kg N ha1 respectively. Maize cv. Abelehii was grown in a poly bag filledwith 15 kg soil. Eight plants per treatment were selected randomly and used for the collection of data on growth parameters forth-nightly. At physiological maturity two plants per treatment were also selected randomly from each treatment plot for yield data. The results showed that TE of maize (Z. mays) varied for the different treatments and these are 6.9 Pa in soil (S) alone to 8.6 Pa in ECO. Increase in N application rate increased TE at the vegetative phase for fast nutrient releasing fertilisers (DFS, ECO, EC, NPK + (NH4)2SO4, (NH4)2SO4) and at the reproductive phase for slow nutrient releasing fertilisers (C and CO). Water-use efficiency increased significantly as rate of N application increased. Treatment ECO improved crop WUEcwu and was 11% and 4 times higher than that forNPK + (NH4)2SO4 or soil alone; and 18-36% higher than those for DFS and CO. Treatment ECO used less amount of water to produce drymatter yield (DMY) and grain yield (GY) that was 5.2%and 12.6%, respectively, higher thanNPK + (NH4)2SO4. Similarly, the DMY and GY for ECO was 8.9-18.5% and 23.4-34.7%, respectively, higher than DFS and CO. High nutrient (N and K) uptake, TE, and low leaf senescence accounts for 83% of the variations in DMY whereas WUEcwu accounts for 99% of the variations in GY. Thus, the study concluded that different sources of fertiliser increased TE and WUEcwu of maize differently as N application rate increases.